Two New Austocystin Analogs from the Marine‐Derived Fungus Aspergillus sp. WHUF05236. Issue 6 (3rd May 2022) - Lv, Huawei; Zhang, Jinkun; Xue, Yaxin; Li, Songwei; Sun, Xiaoyu; Jia, Jia; Bi, Hongkai; Wang, Shoubao; Su, Haibo; Zhu, Mengdi; Wang, Hong; Hong, Kui; et al.
Abstract: Two new austocystin analogs, austocystin P (1 ) and austocystin Q (2 ), along with fourteen known compounds (3 –16 ) were isolated from the fermentation extract of Aspergillus sp. WHUF05236. The planar structures of 1 and 2 were elucidated through 1D, 2D NMR and MS analyses. Their absolute configurations were determined by the time‐dependent density functional (TDDFT)‐ECD calculation. Compounds 3, 11, and 12 exhibited antimicrobial activities against Helicobacter pylori with MIC values ranging from 20.00 to 43.47 μM. Compounds 3, 6, and 7 showed cytotoxicities against the human colon cancer cell lines Hct‐116 with IC50 values of 101.79, 65.46, and 36.72 μM, respectively. Abstract :